A Case Report on Rett's Syndrome - Soumitra Ghosh; Jyotirmoy Sarma; Debdutta Nayak; Tanveer Dabria (Indian Journal of Private Psychiatry)
Introduction: Rett's syndrome is a neurodevelopmental disorder that occurs almost exclusively in females and has a typically deteriorating course that is mostly caused by an identifiable mutation of the MECP2 gene located in the X chromosome. The most characteristic features are loss of purposive hand movements and acquired fine motor-manipulative skills along with lack of language development, distinctive stereotyped movement, episodes of hyperventilation, etc. Case description: Here, we are presenting a case of Rett's syndrome in a girl of 4 years 10 months who had presented to the psychiatry OPD of Tezpur Medical College and Hospital on being referred from the Department of Pediatrics. There was a history of loss of hand skill and speech with purposeless stereotypic movement of hand, as a result of which she was unable to hold objects in her hand. She had broad-based gait with teeth grinding and a history of episodic hyperventilation. To our knowledge, this has been the second case of Rett's syndrome from the eastern zone of India. The first case was reported by Ghosh S et al. from a medical college in Assam. Conclusion: Rett's syndrome is a relatively rare disease with a deteriorating and progressing course without any specific treatment for it. Management plans should be focused on early detection and symptomatic treatment in the form of seizure control, behavior therapy, physiotherapy, etc., along with proper genetic counseling and parental counseling.